A pathway for the biosynthesis of straight and branched, odd- and even-length, medium-chain fatty acids in plants. - Kroumova, A B (1994)
Pathways and enzymes of fatty acid synthase-mediated, long-even-chain (generally C16-C20) fatty acid synthesis are well studied, and general metabolism involved in short-chain (C4-C7) fatty acid biosynthesis is also understood. In contrast, mechanisms of medium-chain (C8-C14) fatty acid synthesis are unclear. Recent work suggests involvement of chain-elongation-terminating thioesterases in medium-chain fatty acid formation in oilseeds and animals. We have shown that iso- and anteiso-branched and straight, odd- and even-length, short-chain fatty acids esterified in plant-trichome-gland-produced sucrose esters are synthesized by using carbon skeletons provided by modified branched-chain amino acid metabolism/catabolism. The principal enzymes involved are those catalyzing leucine biosynthesis in all organisms and those leading to short-chain alcohols in mutant yeasts and alkyl acids in Clostridium species (products often serving as mammalian pheromones). Here we provide evidence that C10-C12 straight medium-chain and C10-C12 branched medium-chain acyl acids of tomato, C6-C8 straight-chain acyl acids of Petunia, and C6 and C8 branched acyl acids of Nicotiana glutinosa are formed by alpha-ketoacid elongation without participation of fatty acid synthase-mediated reactions or -independent thioesterases. This different metabolism suggests greater integration of amino acid and fatty acid metabolism than previously considered and provides other avenues to study and manipulate not only straight even-length but also odd- and even-length straight and branched medium-chain fatty acid biosynthesis.